Safety and benefits of inhaled hypertonic saline following airway challenges with endotoxin and allergen in asthmatics. (21st October 2017) - Alexis, Neil E.; Bennett, William; Peden, David Blaine
ABSTRACT: Objective: To determine whether induced sputum (IS) with hypertonic saline inhalation is safe to use in asthmatics within 24 hours of two commonly used airway challenges, namely endotoxin and dust mite allergen, and to assess whether IS can enhance mucociliary clearance (MCC) rates in asthmatics. Methods: IS (three 7-minute inhalation periods of 3%, 4%, and 5% hypertonic saline) was employed before (N = 29) and within 24 hours of inhaled challenges with endotoxin ( N = 13) and dust mite allergen ( N = 12) in a cohort of mild to moderate asthmatics. Safety was assessed by lung function (Forced Expiratory Volume in 1 second; FEV1) and MCC was measured using a radiolabeled gamma scintigraphy method (Tcm99 sulfur colloid). IS was performed pre and post MCC. Results: No significant lung function decrement was observed before or after inhaled challenges with endotoxin or dust mite allergen. IS significantly enhanced MCC rates before and after inhaled endotoxin challenge. Conclusion: Based on a small cohort, IS is safe to use in mild to moderate asthmatics before and within 24 hours of inhaled challenges with endotoxin and dust mite allergen. Furthermore, IS has beneficial effects on host defense function in asthmatics by enhancing MCC rates.